Kerjaya Wanita Islam dalam Bidang Penyiaran: Cabaran dan Prospek - Abd. Ghani, Zulkiple (Jurnal Usuluddin, 2006)
Working women is a growing phenomenon due to the increase of educational and job opportunities. In broadcasting, women are involved as the main player such as producers and managers, and some of them play active role behind the scene. This article discusses the issues affecting Muslim women working in broadcasting field by looking at the challenges that they have to face and also at their prospect. The study in TV3 shows that women have to manage their working time and family wisely and are facing some difficulties in adhering to the teachings of Islam.